Kebijakan Hukum Match Fixing Pada Sepak Bola Indonesia: Studi Perbandingan Australia dan Jerman - Vicko Taniady; Dina Tsalist Wildana; Reni Putri Anggraeni; Novi Wahyu Riwayanti (University of Udayana, 2022)
Match fixing often colors football in various worlds, including Indonesia. Match fixing is motivated by bribery transactions. This study will explain the match fixing arrangements in various countries, particularly in Indonesia, Australia, and Germany, to provide and build an ius constituendum in the future, especially related to legal subjects, criminal acts, and punishments. The research method in this paper is normative law with a normative and legislative approach and a match fixing policy on comparative law in Indonesia, Australia, and Germany. This study shows that match fixing regulations in Indonesia are still relatively weak, which increases match fixing actions. This can be seen from the regulation of the Criminal Code, which still does not comprehensively regulate the proper legal subjects, and the weakness of the sentences imposed. If you look at the country of Australia, the country has a special regulation to regulate match-fixing called the National Match-Fixing Policy in Sport which was passed in 2011. On the other hand, Germany was an initially prosperous country with score-fixing; the syndicate was able to deal with match-fixing issues with amendments. German Penal Code and Co-founded against match-fixing – a game does not fix program focused on preventive measures, workshops, rules and regulations, ombudsman, and monitoring. By looking at the policies taken by Australia and Germany, it should be a guideline for Indonesia in eradicating the crime of match-fixing. Match fixing sebagai tindakan pengaturan skor kerap mewarnai olahraga sepak bola diberbagai dunia termasuk di Indonesia. Match fixing dilatarbelakangi oleh transaksi suap. Penelitian ini akan menjelaskan pengaturan match fixing diberbagai negara terkhusus di Indonesia, Australia dan Jerman dalam rangka memberikan dan membangun ius constituendum ke depan khususnya terkait subyek hukum, tindak pidana dan pemidanaan. Metode penelitian dalam penulisan ini adalah hukum normatif dengan menggunakan hukum normatif dan pendekatan peraturan perundang-undangan dan comparative law kebijakan match fixing di Indonesia, Australia dan Jerman. Hasil penelitian ini menujukkan bahwa pengaturan tindakan match fixing di Indonesia masih tergolong lemah, yang mengakibatkan semakin meningkatnya tindakan match fixing. Hal tersebut terbukti dari pengaturan Undang-Undang Tindak Pidana Suap yang masih belum mengatur secara komprehensif subjek hukum yang jelas, dan lemahnya hukuman yang dijatuhkan. Apabila melihat negara Australia, negara tersebut memiliki regulasi khusus untuk menangani match fixing yang bernama National Policy on Match Fixing in Sport yang disahkan pada tahun 2011. Di sisi lain, Jerman sebagai negara yang awalnya marak dengan sindikat match fixing mampu menghadapi masalah match fixing dengan amandemen The Germany Criminal Code serta membentuk program Together against match fixing – don’t fix the game yang berfokus pada tindakan pencegahan, workshop, rules and regulation, ombudsman and monitoring. Dengan melihat kebijakan yang diambil oleh Australia dan Jerman, sudah seyogyanya menjadi pedoman bagi Indonesia dalam memberantas tindak pidana match fixing.